Penanggulangan Kesehatan Dalam Kondisi Pasca Bencana Dusun Ujung Indah, Desa Cilellang, Kecamatan Mallusettasi, Kabupaten Barru - Amran Nur; Veronica Margareth Dampung (INDRA: Jurnal Pengabdian kepada Masyarakat, 2020)
Abstract: Indonesia has been declared as one of the most disaster-prone countries according to the United Nations International Strategy for Disaster Reduction. Indonesia ranks 6th among countries prone to disasters. Indonesia is prone to natural disasters such as earthquakes, tsunamis, volcanic eruptions, and others as well as non-natural disasters such as floods, infectious diseases, forest fires, and others, as well as social disasters in the form of social conflicts in various regions. One of the concepts of disaster management is disaster risk management, At this stage, efforts should be made if a catastrophic event occurs, damage and losses with a large enough scale of impact can be avoided and minimized by mitigating education to the community. Because the location of this village is on the seashore and has a watershed that could threaten the safety of the population, therefore a health prevention socialization will be carried out if at any time an unwanted natural disaster occurs. Keywords: natural disasters, Barru Districts, disaster risk, countermeasures.